Sustainable economic development : green economy and green growth (Springer, 2017)
This book introduces the influence and impacts of green economy and green growth on sustainable economic development. Combining empirical and theoretical information, it provides detailed descriptions of state-of-the-art approaches, methods and initiatives from around the globe that illustrate green policies and demonstrate how green growth can be implemented on an international scale. It also includes analyses of specific issues, such as public policies and sustainable development plans that influence industry and increase trade in environmental goods and services - the way to a greener economy, green tourism, green agriculture, green learning and green equilibrium in modern society. Matters such as green procurement, environmentally oriented implementation strategies, and the importance of employee skills in the development of a sustainable future workforce are described, as well as a selection of tools that can be used to foster sustainable growth, green economies and green growth. The book also offers a timely contribution to the dissemination of approaches and methods that improve the way we perceive and utilize natural resources and the technologies designed to protect them. Puts forward new ideas for creating a more sustainable future.
Keywords: Economic development.; Sustainable development.; Environmental policy.; elektronické knihy; electronic books